2008
DOI: 10.1111/j.1478-3231.2008.01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection in pregnant woman and its clinical implication

Abstract: Occult HBV infection shows a difference in prevalence rate depending on the test method but the existence has been confirmed by sequencing analysis. Our results also suggest that vertical transmission through the cord blood is not so high as to be clinical problems and warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
1
20
1
Order By: Relevance
“…In comparison with the prevalence of hp HBI among the pregnant women (approximately 3% to 4% [L.-N. Tao, personal communication]) and in the general population (7.2%) (2), the prevalence of hn HBI among the pregnant women is not statistically insignificant or is even higher (38), as indicated also by our results showing that the hn HBI prevalence was 10.2% (6/59) among the tested mothers. And the inability to routinely identify hn HBI in prenatal women means that they would be treated as non-HBV cases and that their newborns would receive the less effective HBV vaccination protocol (4).…”
Section: Discussionsupporting
confidence: 49%
“…In comparison with the prevalence of hp HBI among the pregnant women (approximately 3% to 4% [L.-N. Tao, personal communication]) and in the general population (7.2%) (2), the prevalence of hn HBI among the pregnant women is not statistically insignificant or is even higher (38), as indicated also by our results showing that the hn HBI prevalence was 10.2% (6/59) among the tested mothers. And the inability to routinely identify hn HBI in prenatal women means that they would be treated as non-HBV cases and that their newborns would receive the less effective HBV vaccination protocol (4).…”
Section: Discussionsupporting
confidence: 49%
“…Cord blood obtained from four of six individuals who were positive with both the HBV DNA methods, was HBV DNA negative. 56 Thus, the vertical transmission of occult HBV infection through cord blood although possible is not so high as to be a clinical problem, but warrants further investigation in population-based studies.…”
Section: Occult Hepatitis B Virus Infectionmentioning
confidence: 99%
“…Many studies have shown that prevalence of occult HBV infection in HBV endemic areas is higher than in Western countries, and the differences in its prevalence might be closely related to the endemicity of HBV infection [10,11] . In Korea, there have been some recent reports of occult HBV infection in outpatients of gastroenterology clinic [12] or in pregnant women [13] ; however, data in general populations are not available. The data in general populations are also limited worldwide [11] , especially for anti-HBc-negative healthy subjects.…”
Section: Introductionmentioning
confidence: 99%